2018
DOI: 10.1017/wet.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Quantify Herbicide Volatility

Abstract: Herbicide active ingredients, formulation type, ambient temperature, and humidity can influence volatility. A method was developed using volatility chambers to compare relative volatility of different synthetic auxin herbicide formulations in controlled environments. 2,4-D or dicamba acid vapors emanating after application were captured in air-sampling tubes at 24, 48, 72, and 96 h after herbicide application. The 2,4-D or dicamba was extracted from sample tubes and quantified using liquid chromatography and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…It has been observed, for example, that inside hermetically sealed environments, relative humidity can rapidly increase, reaching up to 90%, and may affect the gas exchange dynamics and respiration in plants 41 . Furthermore, it has been shown that concentration of dicamba suspended in air decreases as relative humidity raises from 20 to 50% during 48 h after application 18 .
Figure 6 Dicamba injury symptoms observed in exposed soybean plants.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed, for example, that inside hermetically sealed environments, relative humidity can rapidly increase, reaching up to 90%, and may affect the gas exchange dynamics and respiration in plants 41 . Furthermore, it has been shown that concentration of dicamba suspended in air decreases as relative humidity raises from 20 to 50% during 48 h after application 18 .
Figure 6 Dicamba injury symptoms observed in exposed soybean plants.
…”
Section: Resultsmentioning
confidence: 99%
“…A new methodology was proposed to evaluate herbicide volatility based on methodology recommendations by Reynolds 17 and adaptations described by Ouse et al 18 . Herbicides and adjuvant tank-mixtures combinations (Table 1 ) were applied using the MUG 11003 nozzle.…”
Section: Methodsmentioning
confidence: 99%
“…Others have also employed plant bioassays as indicators of dicamba activity (Egan and Mortensen 2012;Penner and Michael 2014;Sciumbato et al 2004). Although the sensitivity of these bioassays is adequate, a quantitative assessment via air sampling followed by chemical extraction and analysis may yield more direct indications of herbicide behavior (Mueller et al 2013;Mueller 2015;Ouse et al 2018). This research aimed to examine the effect of temperature, dicamba formulation, and glyphosate addition on dicamba concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…To fully evaluate air sample extraction, we performed vapor chamber experiments using glass plates ( Figure 4 ) similar to those conducted with plants in other herbicide volatility studies [ 6 , 23 ]. Glass plates with a surface area of 190 cm 2 were sprayed with selected dicamba formulation using a single-nozzle, track-mounted research sprayer calibrated to deliver 140 L ha −1 per pass using a Turbo Teejet Induction nozzle (TTI 11002) (Teejet Technologies, Springfield, IL, USA).…”
Section: Resultsmentioning
confidence: 99%
“…Sub-picogram level detection of dicamba from water was also reported using paired-ion electrospray ionization (ESI) mass spectrometry [ 14 ]. Furthermore, several MS-based dicamba analytical methods have been reported for food items [ 17 , 18 ], water and agricultural cleanouts [ 13 , 14 , 16 , 19 , 20 , 21 , 22 ], air samplers [ 6 , 23 , 24 ], crops like apple, pepper, brown rice, and soybean [ 25 ], tobacco [ 26 ], barley [ 27 ], soybean [ 28 ], rice [ 29 ], as well as in other agricultural commodities [ 30 ]. Most of these protocols rely on triple quadrupole and/or higher resolution MS instruments, although quantification procedures using LC–diode array detection (DAD) [ 24 ] and single-quadrupole LC–MS [ 6 , 31 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%